Developing English Writing Materials in Narrative Text Based on Genre-Based Approach - Sinaga, Ismi Novitasari; Fitriyani, Tri (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2019)
This study aims to develop appropriate English writing materials by using Genre-Based Approach. This study was conducted by Research and Development (R&D) design through six stages; gathering data and information, analyzing data, designing new materials, validating by experts, revising and final product. It was conducted at SMA Negeri 14 Medan for grade XI, consisting of 32 students. Instrument for collecting data was document, questionnaire and interview. Based on the data, it found some writing material, which has inappropriate instruction related to writing a text that should be developed based on syllabus and students? needs. In analyzing students? needs, the questionnaire was distributed to 32 students and also conducting an interview to the teacher and students. Then, the researchers design the new materials that validated by experts. The results of validating show 91,6% from English lecturer and 80% from English teacher. It means the developing materials are categorized as ?relevant? for the grade XI students at SMA Negeri 14 Medan.